Percutaneous Exposure Incidents Among Vietnamese Hospital Personnel and the Impact of a Prevention Program - Thu, Le Thi Anh; Trang, Dang Thi Van; Thoa, Vu Thi (International Journal of Infection Control, 2007)
The establishment of a reporting system and management of percutaneous occupational exposures management in a Vietnamese tertiary hospital has been achieved in encouraging the healthcare personnel (HP) to report their occupational exposures and practicing safety practice. Despite the increasing number of HIV positive patients being admitted to the hospital, the comprehensive occupational exposure prevention program, involving supplying sufficient protective barrier equipment and needle disposal units and continuing educational programs for all hospital staff on the use of these equipment has been successful in preventing HIV occupational exposures. Dedicating resources to occupational exposure prevention and HP safety should be a priority for clinical care and treatment programs in Vietnam.